Readers and text worlds of dystopia - Hasan, Arwa (2017)
This thesis is an exploration of reading styles and stylistic patterning in relation to dystopian fiction. Situated within an empirical cognitive poetics, the study draws upon naturalistic reader-response data, with specific reference to Atwood’s The Handmaid’s Tale and Vonnegut’s ‘Harrison Bergeron’, as case studies of dystopian texts that produce a spectrum of readings. The notions of preferred and dispreferred responses are defined in cognitive linguistic and pragmatic terms, and non-normative readings of these dystopian texts are investigated. The thesis adopts a text-world theoretical description, and provides both naturalistic reader-community data as well as focused interviews and reading protocols. It was found that some readers insist on producing dispreferred readings even in the face of lack of textually-driven evidence. Such readers allow their own emotions, outlooks and dispositions to over-ride the textual patterning, in producing dispreferred and non-evidential readings. These readings are nevertheless genuinely held. This study raises questions for all text-driven models of literary reading and analysis.